Reforma a vapor do etanol sobre catalisadores Cu-Ni/ZnO - Barbosa, Elysabeth Fontoura (Universidade Federal de São Carlos, 2008)
In this work copper, nickel and copper/nickel supported in zinc oxide catalysts were prepared, characterized and tested in the steam reforming of ethanol to produce hydrogen. The support and the supported catalysts were prepared by precipitation and impregnation methods, respectively, using aqueous solution of copper and nickel nitrates. The supported catalysts were prepared by varying the nickel and copper loading to obtain 15% weight of metals in the final solid. After prepared and calcined, the solids were characterized by Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES), X-Ray Diffraction (XRD), Nitrogen Adsorption by B.E.T. method, and Temperature Programmed of Reduction with H2 (TPR-H2). The results indicated that the preparation method and the treatment conditions were appropriated to achieve the designed catalytic samples. The catalytic tests were carried out in a range of temperature of 300 to 650oC and water:ethanol molar feed ratio of 3:1 and 6:1. It was verified that the ethanol conversions were higher then 80% in all range of temperature for all catalysts, including the support, independently of water:ethanol molar feed ratio. Other parallel reactions were observed, rather than steam reforming of ethanol, at different conditions of operation, like dehydrogenation of ethanol to acetaldehyde and hydrogen, decarbonylation of acetaldehyde to CH4 and CO, decomposition of ethanol to CH4, CO and H2, water-gas shift and methane reforming at high temperatures. It was also observed that the best combination between metal loading and process parameters to produce hydrogen from steam reforming of ethanol was in the temperature range of 450 to 550oC, 6:1 molar water:etanol feed ratio and bimetallic catalysts with the composition Cu7,5Ni7,5ZnO.
Keywords: Catalisadores; Reforma à vapor; Hidrogênio; ENGENHARIAS::ENGENHARIA QUIMICA